Content of the course and methodology of individual work on mathematical programming in pedagogical university (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2020)
The article describes the content and methodology of teaching mathematical programming to students of IT specialties of pedagogical universities. The peculiarities of organizing the individual work of students who study according to the dual system by using the elements of "flipped" learning through e-learning courses are considered.The subject of studying the course "Mathematical Programming" is the basic information about the problems of mathematical programming, classical methods of optimization of functions of one and many variables, review of the basic formulations, methods of researching and solving problems of linear, nonlinear, integer, discrete, stochastic as well as modern information systems and technologies that are used in researching and solving specific applications of mathematical programming.This course is designed for master students of the 2nd year of studying in informatics specialities who have mastered basic mathematical and informatics courses.Students studying according to the dual system and working in institutions of secondary education will learn respective disciplines according to individual plans (schedules).To effectively organize the individual work of students within mathematical programming course students should develop, implement, and protect their individual or group projects to solve specific optimization problems.Another effective way of organizing students' individual work is through the use of digital technologies, including flipped learning, and through various e-learning courses.The article provides examples of implementating the tasks of the individual project "Setting, researching, solving and analysing nonlinear programming problems" in the Maple computer mathematics system environment.
Keywords: math programming; individual project; inverted learning; Maple computer math system